Targeting HMGB1-mediated autophagy as a novel therapeutic strategy for osteosarcoma - Huang, Jun (Landes Bioscience, 2012)
Autophagy is a catabolic process critical to maintaining cellular homeostasis and responding to cytotoxic insult. Autophagy is recognized as “programmed cell survival” in contrast to apoptosis or programmed cell death. Upregulation of autophagy has been observed in many types of cancers and has been demonstrated to both promote and inhibit antitumor drug resistance depending to a large extent on the nature and duration of the treatment-induced metabolic stress as well as the tumor type. Cisplatin, doxorubicin and methotrexate are commonly used anticancer drugs in osteosarcoma, the most common form of childhood and adolescent cancer. Our recent study demonstrated that high mobility group box 1 protein (HMGB1)-mediated autophagy is a significant contributor to drug resistance in osteosarcoma cells. Inhibition of both HMGB1 and autophagy increase the drug sensitivity of osteosarcoma cells in vivo and in vitro. Furthermore, we demonstrated that the ULK1-FIP200 complex is required for the interaction between HMGB1 and BECN1, which then promotes BECN1-PtdIns3KC3 complex formation during autophagy. Thus, these findings provide a novel mechanism of osteosarcoma resistance to therapy facilitated by HMGB1-mediated autophagy and provide a new target for the control of drug-resistant osteosarcoma patients.